Research on Governance of Sports Department and Training Faculty of Teacher Training and Education - A, Palmizal; Setiawan, Iwan Budi; Astria, Rani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Governance of the Department of Sports and Coaching in the Faculty of Teacher Training and Education includes aspects of planning, implementation, evaluation, and follow-up in both academic and non-academic management. This study employed a qualitative approach with data collection techniques including interviews, observations, and document analysis. The research subjects involved department leaders, lecturers, and administrative staff. The findings reveal that the department's governance has been implemented fairly well, although some weaknesses were identified in the monitoring system and coordination among implementing units. In addition, the follow-up actions from evaluation results have not been optimal in improving the quality of academic services. Therefore, a strategy to strengthen performance-based management and a more integrated reporting system is needed.